Economic Drivers of International Migration to Türkiye: A Regional Comparison Study - Gündoğmuş, Bekir; Bayir, Musa; Sarihan, Ahmed Yusuf (Makara Human Behavior Studies in Asia, 2026)
This study investigates the macroeconomic determinants of registered international migration to Türkiye by employing panel data regression techniques at the NUTS-2 regional level for the period 2016–2022. The results reveal that per capita income, employment, and the share of industry, services, and construction sectors in total production have a statistically significant and positive impact on migration inflows, while inflation exhibits a negative effect. However, agricultural production proportion and export performance do not appear to significantly influence regional migrant preferences. Causality tests further support the existence of both bidirectional and unidirectional relationships between economic indicators and migration. The findings underscore the importance of economic motivations in shaping migrants’ regional settlement choices, particularly for those who, after fleeing political instability in their home countries, choose to remain in Türkiye long-term. This research contributes to the limited body of macro-level empirical studies on migration in Türkiye and offers policy-relevant insights for developing regionally differentiated migration strategies.